2018
DOI: 10.1111/jop.12707
|View full text |Cite
|
Sign up to set email alerts
|

Role of p38 MAPK in disease relapse and therapeutic resistance by maintenance of cancer stem cells in head and neck squamous cell carcinoma

Abstract: This study demonstrated that p38 MAPK activation may play a role in therapeutic resistance and disease relapse in HNSCC by maintenance of CSCs phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 28 publications
2
23
0
Order By: Relevance
“…Our data revealed that CSC_EVs increased CDDP resistance, metastasis, and the self-renewal capability of OSCC CAL27 and SCC-15 cells, with a concomitant increase in expressions of several oncogenic markers such as PI3K, STAT3, mTOR, TGF-β1, and the stemness marker β-catenin, in CAL27 and SCC-15 cells after their coculture with CSC_EVs. These findings are consistent with those of previous studies that demonstrated that enhanced PI3K/mTOR/STAT3 signaling promotes chemoresistance, stemness, and the metastatic potential of oral cancer cells [25,29].…”
Section: Discussionsupporting
confidence: 93%
“…Our data revealed that CSC_EVs increased CDDP resistance, metastasis, and the self-renewal capability of OSCC CAL27 and SCC-15 cells, with a concomitant increase in expressions of several oncogenic markers such as PI3K, STAT3, mTOR, TGF-β1, and the stemness marker β-catenin, in CAL27 and SCC-15 cells after their coculture with CSC_EVs. These findings are consistent with those of previous studies that demonstrated that enhanced PI3K/mTOR/STAT3 signaling promotes chemoresistance, stemness, and the metastatic potential of oral cancer cells [25,29].…”
Section: Discussionsupporting
confidence: 93%
“…Knockdown of either p38 or HSP27 enhanced cisplatin sensitivity. In head and neck cancer patients, the upregulation of p38 expression and activation in the surgical resection margin of the tumor is associated with the expression of CSC markers (OCT4, KLF4, MYC, and CD44) and a higher frequency of relapse [135]. Treatment of cultured tumor cells with p38 inhibitors reduced the expression of CSC markers and sensitized the cell to DNA damage induction and cisplatin.…”
Section: P38 Enhancing Resistance To Targeted Therapies and Chemothermentioning
confidence: 99%
“…Upregulation of p38 promotes CSC-like characteristics in osteosarcoma and breast cancer cells [48, 49]. p38 activity is critical for maintaining CSCs traits in head and neck squamous cell carcinoma [22]. Our previous study indicated that TS induced p38 activation in mouse liver tissues [23].…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation of p38 is able to transduce various signals and elicit a wide range of cellular response [21]. Suppression of p38 activity reduced the expression of CSCs markers and sphere formation ability, and decreased migratory potential in head and neck squamous cell carcinoma [22]. Previous study showed that TS triggered MAPK pathways activation in the liver of BALB/c mice [23].…”
Section: Introductionmentioning
confidence: 99%